1983
DOI: 10.1002/app.1983.070280507
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of nylon 6 polymerization in tubular reactors with recycle

Abstract: SynopsisIn the hydrolytic polymerization of t-caprolactam, the ring opening of the monomer is much slower than the polyaddition reaction. Hence, the mixing of aminocaproic acid to the feed results in a faster conversion of the monomer. Industrially, this fact is exploited by using a recycle stream. An isothermal plug flow reactor (PFR) with a recycle is simulated in this study, using two techniques: the method of successive substitutions and Wegstein's method. It is found that, under certain operating conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Considering the economic scale of nylon-6 production, it is not surprising that a number of polymerization models based on first principles have appeared. These models attempt to apply knowledge of kinetics, physical and thermodynamic properties, mass and energy transport, and phase equilibrium to simulate a manufacturing process. We can apply an accurate model to improve the product quality, increase the production rate, and reduce production costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the economic scale of nylon-6 production, it is not surprising that a number of polymerization models based on first principles have appeared. These models attempt to apply knowledge of kinetics, physical and thermodynamic properties, mass and energy transport, and phase equilibrium to simulate a manufacturing process. We can apply an accurate model to improve the product quality, increase the production rate, and reduce production costs.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who recognized the value of simulation began publishing models of nylon-6 polymerization in the 1970s, with Giori and Hayes 4 among the first. Initial models for most commercial nylon polymerization technologies have now been documented, including VK tube, 5 plug-flow, 6 wiped-film, 7 and semibatch reactors. 8 In the modeling of any multiphase chemical manufacturing process, it is important to properly model the phase equilibrium of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Sitting1 has summarized the evolution of various reactors ranging from batch reactors operating under high pressure (to avoid vaporization) to cascades of stirred tank reactors in combination with tubular reactors. In the last several decades, a considerable amount of research has been reported on the simulation and optimization of nylon 6 reactors 2–16. And meanwhile, most of earlier functional studies focused attention on isothermal reactors without vaporization of water and other low‐molecular‐weight compounds and have helped spawn the values of rate and equilibrium constants for various main and side reactions associated with the hydrolytic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…To name a few, Tai and co‐workers15–19 have supplied the best‐established thermodynamics and kinetic constants and studied some commonly used industrial reactors. Gupta et al10–14 have simulated several kinds of single tubular reactors, on the basis of a comprehensive chemistry scheme. Besides three main reactions: ring‐opening, polycondensation, polyaddition, it includes such commercially important side reactions as chain‐ending reaction which regulates the molecular weight of the polymer produced by adding small amount of acids, and reactions forming cyclic oligomers which are undesirable materials for spinning and molding the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that the temperature distribution affected the molecular weight distribution. Gupta et al (1983b) also investigated the polymerization of nylon-6 in tubular reactors. They modeled the use of recycle to increase the rate of polymerization.…”
Section: Introductionmentioning
confidence: 99%